Nobelova nagrada za razvoj fizikalne kozmologije - Fabjan, Dunja (Obzornik za matematiko in fiziko, 2021)
Half of the Nobel Prize in Physics 2019 was awarded to James Peebles, professor at University of Princeton, for "theoretical discoveries in physical cosmology", who shared the award with the discoverers of the first planet observed around a Solar-type star. This article presents the historical frame where the Nobel Laureate developed his research. Since he tackled a number of different research topics I decided to emphasise selected themes, where contributions of his research represented a breakthrough and established the basis for the development of physical cosmology.
Keywords: fizikalna kozmologija; kozmologija